P459 Vedolizumab for the treatment of chronic pouchitis: the Edinburgh experience. (25th January 2019) - Cesano, S; Jones, G R; Jenkinson, P W; Shand, A G; Lees, C W; Arnott, I D; Plevris, N
Abstract: Background: Pouchitis is the most common complication following ileal pouch-anal anastomosis (IPAA) formation for medically refractory UC. Despite most patients responding to antibiotics, 10–15% of patients will develop chronic debilitating pouchitis that becomes antibiotic dependant or refractory to antibiotics and immunosuppressive therapy. Vedolizumab is a gut selective a4b7 anti-integrin biologic that offers a potential new mechanism for the treatment of chronic pouchitis. Therefore, the aim of this study was to evaluate the effectiveness of vedolizumab for the treatment of chronic pouchitis Methods: This was a retrospective case series performed at a tertiary IBD centre in Edinburgh, UK. All patients started on vedolizumab for the indication of antibiotic dependant or treatment refractory (failed antibiotic therapy ± immunomodulator or anti-TNF) pouchitis following IPAA for active UC were included. All patients had active pouchitis, defined by a pouchitis disease activity index (PDAI) >7. Baseline characteristics were collected via review of electronic medical records. Assessment of improvement was determined by the treating physician at last follow-up (score: '0' no improvement; '1' mild; '2' moderate; '3' excellent). Differences in the PDAI clinical subscore and faecal calprotectin levels between baseline and last follow-up were also analysed using the Wilcoxon signed rank test. Results: Seven patients were included (4 females, 3 males; median age 51 years [IQR 48–59]) with a median follow-up of 46 weeks (IQR 29–106). Of these, 6 patients were started on vedolizumab for the treatment of refractory pouchitis whilst 1 patient was started for antibiotic dependant disease. All patients remained on vedolizumab at the end of follow-up. Median PDAI at baseline was 9 (8–10). At last follow-up 0%, 42.9% ( n = 3/7), 14.3% ( n = 1/7) and 42.9% ( n = 3/7) were deemed to have no, mild, moderate and excellent improvement, respectively. The mean PDAI clinical sub-score fell significantly from 5 to 2 (Figure 1A). The mean faecal calprotectin levels also fell significantly from 618 µg/g to 129 µg/g (Figure 1B). At last follow-up, 85.7% ( n = 6/7) required no further antibiotic treatment since initiating vedolizumab including the patient with previously antibiotic dependant disease. Arthralgia was the only reported adverse event ( n = 2). Conclusions: Vedolizumab is an effective and well-tolerated treatment option for chronic refractory pouchitis.